Can your foot function as a brain? - Wan Hasan, Wan Zuha; Hussien, Omar; Sabry, Ali; Mohamad Ghazali, Aina Mardhiyah (Universiti Putra Malaysia Press, 2016)
Data from WHO shows that about 300 million of the world’s population had diabetes in year 2010, of which 3.4 million was from Malaysia. Often, people with diabetes are more likely to experience foot problem because of nerve damage resulting from poor blood circulation. Delay in detection and treatment will lead to other complications that lead to amputation of lower limbs.